ARCHITECTURAL SCULPTED DECORATION OF CIVIL BASILICA IN ANCIENT MUNICIPALITY DD (Heritage, 2020)
On the occasion of the systematic archaeological research of the forum at the ancient site of the Municipium DD in the north of Kosovo and Metohija, one of the rare examples of a civil basilica was discovered, along with the unusual forms of late antique decorative architectural elements within it. The colonnades from the interior of the basilica consisted of as many as three types of different columns - with a rectangular, oval, and circular base. Each of the examples of these columns had the appropriate bases and capitals, which in their appearance deviate from the most common design of these elements within ancient columns. In this paper, we have determined the place and course of development of specific forms of architectural sculpture in this site.The analysis highlights particular architectural details that determine the identification of the stylistic order to which the forms of our capitals and bases are closest. The special motifs that appear in the form of flutes and lunulae on the capitals determine that the decorative stone sculpture from the civil basilica of Municipium DD belongs to the Doric style. In an attempt by a stonemason to define the shapes of a special type of this order, that is the so-called palm "Pergamon" capitals, it is recognizable that he gave up more demanding details such as leaf ends, which are otherwise characterized by this type. Despite the general affiliation with the Roman Doric architecture, the individual approach of the stonemasons in shaping the capitals meant that certain features were noticed on them, which have not been recognized in other archaeological sites in the Balkans so far. At the same time, on the bases of columns with a circular and oval base, a lack of trochilus and listels, common for shaping ancient bases, is noticeable.
Keywords: Municipium DD, civil basilica, late antique architecture, Doric order.